Nature and Dynamics of Stock Market: A Bibliometric Analysis of its Development and Operations as an Economic Agency - Karki, Dipendra; Bhattarai, Ganesh; Khadka, Prajjwol Bikram (NCC Journal, 2023)
This study methodically examines the pivotal role of stock markets in global economies, emphasizing their evolution from theoretical concepts to essential economic infrastructure. It employs advanced bibliometric tools and analysis, including co-authorship, citation, bibliographic coupling, and visual mapping techniques using VosViewer, to explore into stock market research from 1990 to 2023. The findings offer unprecedented insights into the academic and practical fields of stock market research. These analyses explore detailed collaboration networks, influential research contributions, and thematic clusters, highlighting the dynamic interplay between stock market developments and economic growth. This study documented the multifaceted nature of stock market development, with particular emphasis on four factors: supply, demand, institutions, and economic policies. The findings also emphasize that stock market development is a dynamic and long-term process, intricately linked to the broader development of a financial system. Although stock markets are primarily a private sector endeavor, the government’s supporting role is pivotal for their success. The integration of this framework not only enriches our understanding of stock market dynamics but also charts the course for future research directions in the field, emphasizing the importance of interdisciplinary approaches and global research collaborations in advancing our understanding of financial systems.